PELATIHAN DAN PEMBINAAN KOMERSIALISASI PRODUK USAHA MIKRO AGRIBISNIS UNTUK MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 PADA KELOMPOK TANI MEKAR KEMBALI SERENTAK DESA RAMBAHAN BATANGHARI JAMBI - Enita Enita; Uliya Uliya; Ade Jermawinsyah Zebua (Nindikayla Institute, 2023)
Community service based on the Study Program proposed by the Agrotechnology Study Program, Agribusiness Study Program and Management Study Program of Graha Karya Muara Bulian University is Training and Coaching the Commercialization of Agribusiness Micro Business Products of the Farmer Group Mekar Kembali Rambahan Village, Muara Bulian District, Batanghari Regency, Jambi Province to Face the Era of the Industrial Revolution 4.0. This service activity was carried out because the Mekar Kembali Farmer Group is an area close to the Graha Karya Muara Bulian University Campus. On this occasion, the service that will be carried out is training and coaching the commercialization of products to agribusiness micro-enterprises in the Mekar Kembali Farmer Group, Rambahan Village, Muara Bulian District, Batanghari Regency, Jambi Province. This is done because the era of the Industrial Revolution 4.0 has brought changes to product commercialization methods, so in an effort to capture these good enough commercialization opportunities so that they are not inferior to similar products domestically and abroad, this community service activity is carried out. So that in the end it can expand market share, increase income, and open up new jobs. After this activity was carried out, training participants (agribusiness micro-enterprises) gained additional knowledge about good products and production, commercial products, new marketing networks and product commercialization mechanisms in the digital era of the Industrial Revolution 4.0. Service activities will continue to the coaching stage of packaging improvement, so that products can be marketed digitally